A Complication of an Endoscopic Pigtail Stent Migration into the Cavity during Deployment as a Treatment for Gastric Leak. (10th September 2019) - AlAtwan, Abrar A.; AlJewaied, Ali; AlKhadher, Talal; AlHaddad, Mohannad; Siddique, Iqbal
Abstract : Gastric leak following gastrointestinal surgery is the most dreadful complication, which implies long hospital stay, morbidities, and not irrelevant mortalities. There is no standard recommendation for treating postlaparoscopic sleeve gastrectomy leak, which makes its management challenging. Endoscopic internal drainage by double-pigtail drains currently became the recommended approach. Complications to this approach include bleeding, ulceration at the tip of the double-pigtail stent, and uncommon migration. Here, we report our experience with drain displacement into the cavity while deployment in a patient who experienced gastric leakage after undergoing sleeve gastrectomy.